Azepino-indazoles as calcitonin gene-related peptide (CGRP) receptor antagonists. (1st January 2021) - Mercer, Stephen E.; Chaturvedula, Prasad V.; Conway, Charles M.; Cook, Deborah A.; Davis, Carl D.; Pin, Sokhom S.; Macci, Robert; Schartman, Richard; Signor, Laura J.; Widmann, Kimberly A.; Whiterock, Valerie J.; Chen, Ping; et al.
Graphical abstract: Abstract: Calcitonin gene-related peptide (CGRP) receptor antagonists have been shown clinically to be effective treatments for migraine. Zavegepant (BHV-3500, BMS-742413) is a high affinity antagonist of the CGRP receptor (hCGRP Ki  = 0.023 nM) that has demonstrated efficacy in the acute treatment of migraine with intranasal delivery in a Phase 2/3 trial, despite showing low oral bioavailability in rats (FPO  = 1.7%). Using zavegepant as a template, we sought to improve oral bioavailability through a series of azepinones which were designed in an attempt to reduce the number of rotatable bonds. These efforts led to the discovery of compound 21 which was able to mostly maintain high affinity binding (hCGRP Ki  = 0.100 nM) and in vivo efficacy in the marmoset facial blood flow assay, while greatly improving oral bioavailability (rat FPO  = 17%).